The Effect of Chamomile Oil on Pain and Anxiety Intensity of IUD Insertion in Women Referring to Karaj Health Centers: Ridit Analysis - Talebi, Atefeh; Akbari, Abolfazl; Kashiha, Mina; Khokarami, Nahid (Archives of Advances in Biosciences, 2019)
Introduction: Intrauterine device (IUD) is a safe, effective and reversible method of family planning. Unfortunately, IUD insertion causes anxiety and pain. The aim of study was to compare ridit analysis and Kruskal-wallis test in pain and anxiety intensity of IUD insertion in women referring to health centers of Karaj (Iran). Materials and Methods: In this randomized clinical trial study, 150 eligible women candidate intrauterine device insertion entered the study and were randomly divided into three groups: chamomile, placebo and control groups. Data was collected from women who came to health centers in Karaj (Iran) in 2017. Data collection tools included demographic information, Spiel-Berger questionnaire and pain visual analogue scale. The intensity of pain and anxiety were measured afterwards. Finally, ridit analysis and Kruskal-wallis test were used to rank the intensity of pain and anxiety in patients. The R-3.4.3 and Microsoft’s Excel software were used for statistical analysis. Results: The results showed that the mean±SD of age in three groups was 29.7±7.01, 28.68±8.15 and 31.6±7.71, respectively. Ridit analysis and Kruskal-wallis test showed considerable decrease of the anxiety and pain intensity, induced by IUD insertion in Chamomile, Placebo and Control groups respectively. Ridit analysis and Kruskal-wallis test statistics are significant. The value of the ridit statistic was <!–?mso-application progid="Word.Document"?–> 15د‡2=20.23, P<0.001"> and the value of Kruskal-wallis test is <!–?mso-application progid="Word.Document"?–> 15د‡2=18.67, P<0.005"> in pain intensity. Moreover, the value of the ridit statistic is <!–?mso-application progid="Word.Document"?–> 15د‡2=3.92, P<0.001"> and the value of Kruskal-wallis test is <!–?mso-application progid="Word.Document"?–> 15د‡2=21.37, P<0.005"> in anxiety intensity. Conclusions: The results of this study suggested that, there is less significant difference in ridit analysis than Kruskal-wallis test among the three groups in decreasing pain and anxiety intensity.